New cellular imaging of oocytes and preimplantation embryos using Lumitein™: Evaluation of oocyte quality and new information on protein dynamics within the perivitelline space during the one-cell oocyte stage in mice - Hiroka OKAJI; Kenta TETSUKA; Ren WATANABE; Satoshi KISHIGAMI (The Journal of Reproduction and Development, 2020)
The extracellular matrix between the oocyte and zona pellucida (ZP) plays an important role in mammalian fertilization and preserves the specific environment of the perivitelline space (PVS) during the development of a preimplantation embryo after fertilization. In this study, we applied a highly sensitive luminescent protein dye, LumiteinTM, to observe the hydrophobic status of proteins in oocytes and preimplantation embryos. LumiteinTM is widely used for detecting denatured proteins after sodium dodecyl sulfate-polyacrylamide gel electrophoresis. LumiteinTM fluorescence was detected primarily in the PVS and degenerated first polar body of fresh normal metaphase II (MII) oocytes but much less within the ZP and ooplasm, which suggested a hydrophobic PVS environment in the MII oocytes. Unexpectedly, abnormally-shaped fresh or aged oocytes showed stronger fluorescence in the PVS, which reflected oocyte quality. Interestingly, 10 h after fertilization, the fluorescent signal in the PVS temporarily increased in a patched pattern that appeared and then disappeared by the two-cell stage. After the two-cell stage, the decreased fluorescent signal was maintained throughout the development of the preimplantation embryo. These results suggest new protein dynamics in the PVS during the one-cell stage of the oocyte. Thus, cellular imaging of oocytes and preimplantation embryos using LumiteinTM provides new information on protein dynamics.